ILMU PENDIDIKAN DALAM FILSAFAT PENDIDIKAN BARAT DAN ISLAM - edi purnomo (STAI Al-Hidayat Lasem, 2025)
The arrival of Islam and its proponent Muhammad SAW. In the middle of the year, there was a major revolution in Arab society. Before the arrival of Islam, Arab society was a society that ignored or did not obey human nature. During inter-tribal wars that lasted for decades, girls were buried alive, idols were worshipped, and people with low social status were oppressed by nobles. It has become part of their lives. As if this was his entire outlook on life. Not only that, tribal fanaticism was very strong, women's placement in a very low position was common in their lives at that time.